1999
DOI: 10.1128/jcm.37.5.1536-1547.1999
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Pathologic Evaluation of ChronicBartonella henselaeorBartonella clarridgeiaeInfection in Cats

Abstract: Human Bartonella infections result in diverse medical presentations, whereas many cats appear to tolerate chronic bacteremia without obvious clinical abnormalities. Eighteen specific-pathogen-free cats were inoculated with Bartonella henselae- and/orBartonella clarridgeiae-infected cat blood and monitored for 454 days. Relapsing bacteremia did not correlate with changes in protein profiles or differences in antigenic protein recognition. Intradermal skin testing did not induce a delayed type hypersensitivity r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
146
3
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(168 citation statements)
references
References 36 publications
9
146
3
10
Order By: Relevance
“…Similar results have been observed for cats experimentally infected with B. henselae (23,40). Western blotting has been used both in humans (18,35,36) and cats (20,31) for detection of Bartonella species-specific antibodies. In the present study, at least 12 prominent immunoreactive protein bands were identified when sera from B. koehlerae-infected cats were blotted against B. koehlerae OMPs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results have been observed for cats experimentally infected with B. henselae (23,40). Western blotting has been used both in humans (18,35,36) and cats (20,31) for detection of Bartonella species-specific antibodies. In the present study, at least 12 prominent immunoreactive protein bands were identified when sera from B. koehlerae-infected cats were blotted against B. koehlerae OMPs.…”
Section: Discussionsupporting
confidence: 76%
“…SDS-PAGE analysis has been performed to differentiate and classify Bartonella species and types (31,35,44). Distinctive protein profiles, especially among proteins smaller than 54 kDa, were observed among nine different Bartonella species (35).…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiment, two of three naturally infected cats (Cats A and B) showed relapsing bacteremia and persistent infections. A similar phenomena has been reported in previous reports on naturally infected cats (1) as well as on cats experimentally infected with the peripheral blood from naturally infected cats (16,17). In addition, specific-pathogen free (SPF) cats inoculated with multiple strains containing genetically distinct organisms also showed repeated bacteremia infections (10,30).…”
Section: Discussionsupporting
confidence: 87%
“…Prolonged periods of bacteremia have been documented in naturally infected cats for at least 15 months (Kordick et al 1995) and in experimentally infected cats for at least 454 days (Kordick et al 1999). In a study where female C57BL ⁄ 6 mice were infected with B. henselae, B. henselae-DNA could be detected for 94 days (Regnath et al 1998).…”
Section: Discussionmentioning
confidence: 99%